2020
DOI: 10.33448/rsd-v9i9.8019
|View full text |Cite
|
Sign up to set email alerts
|

Transtornos somatoformes durante a pandemia de COVID-19

Abstract: Objetivo: apresentar os transtornos somatoformes mais comumente observados na clínica médica diária, relacionando-os com a atual situação de pandemia da COVID-19. Métodos: foi realizada uma revisão bibliográfica descritiva e exploratória, de abordagem qualitativa, utilizando os bancos de dados PubMed, LILACS, SciELO e ScienceDirect; com os seguintes descritores: Somatização, Transtornos Somatoformes, Psicossomática, Hipocondria, Transtorno neurovegetativo, Dor crônica, Pandemia, Epidemia, COVID-19, Coronavírus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…The laboratory analysis was conducted using a commercial kit imported by Diasorin (MS Registry: 103.398. [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56], from the Liaison® under batch 354020 and validity 12/15/2020, through the quantitative determination of IgG antibodies against the S1 and S2 proteins of SARS-CoV-2, with the supplier's report of 97.4% sensitivity (percentage of positive hits) and 98.5% specificity (percentage of negative hits). The authors also performed an internal validation test, in addition to following the LACEN-MT biosafety protocols at all testing stages.…”
Section: Administrative Areas Government Control Actions Of Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…The laboratory analysis was conducted using a commercial kit imported by Diasorin (MS Registry: 103.398. [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56], from the Liaison® under batch 354020 and validity 12/15/2020, through the quantitative determination of IgG antibodies against the S1 and S2 proteins of SARS-CoV-2, with the supplier's report of 97.4% sensitivity (percentage of positive hits) and 98.5% specificity (percentage of negative hits). The authors also performed an internal validation test, in addition to following the LACEN-MT biosafety protocols at all testing stages.…”
Section: Administrative Areas Government Control Actions Of Covid-19mentioning
confidence: 99%
“…The increase in somatic symptoms during the COVID-19 pandemic, such as hypochondria, somatization and chronic pain, has been related to impotence arising from the uncertainties of pandemic lifestyle changes 42 . This growth of somatic symptoms in the population raises concern, as there is reported that somatic symptoms can be predictors of suicidal ideas 43 .…”
Section: Variablesmentioning
confidence: 99%
“…Bodily pains without an identifiable physical cause may be the expression of the patient's psychic suffering, and may be symbolically related to the atonement of guilt or suppressed aggression. Pain can function as a method of obtaining love, of punishment for mistakes made and as a compensation for an intimate feeling of being bad (GRACINO et al, 2020) Figure 20 shows activities that people perform to promote their well-being, such as household activities, crafts, meditation, prayer, physical activities, reading and others.…”
Section: Sexmentioning
confidence: 99%
“…Dor de cabeça, sensação de falta de ar, palpitações, tremores, alergia e manchas corporais foram as reações citadas. Somatizações, que abarcam sintomas não explicados pela ciência médica e que são comumente associadas à dificuldade emocional, também estiveram presentes em algumas falas, o que sinaliza a necessidade de abordagens que considerem os fatores biopsicossociais no cuidado às queixas de usuários de serviços de saúde (Gracino, Louveira, Gaudioso, & Souza, 2020).…”
Section: Reações Físicas E Psicoemocionaisunclassified